Platinum nanoparticle-loaded titanium dioxide photocatalyst and application thereof in photocatalytic nitrogen oxide reduction synthesis of ammonia
The TiO2 photocatalyst supported by Pt nanoparticles achieves efficient reduction of NOx in the gas-solid phase, solving the problems of low liquid phase reaction efficiency and secondary pollution of NO3ˉ, improving catalytic activity and selectivity, and meeting the practical application needs.
Patent Information
- Application Number
- CN202411846824.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the liquid phase ammonia synthesis process of NOx has an efficiency bottleneck, and the photocatalytic NOx oxidation product NO3ˉ leads to secondary pollution, affects precipitation acidity and water pollution, and lacks research on the reduction of gas-solid phase NOx ammonia synthesis.
The TiO2 photocatalyst supported by Pt nanoparticles was prepared by precipitation or impregnation method, and was used for gas-solid-phase photocatalyzed NOx reduction to synthesize ammonia, simplifying the reaction system, and adjusting the number of Pt nanoparticles to optimize catalytic performance.
The efficient NOx gas-solid-phase ammonia synthesis is achieved, which avoids the efficiency bottleneck in liquid phase reactions, improves catalytic activity and selectivity, solves the problem of H+ protonation, and enhances the conversion and selectivity of photocatalytic NOx reduction synthesis ammonia.
Smart Images

Figure CN119303564A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to but is not limited to the technical field of catalytic surface interface and photocatalyst preparation, and in particular relates to a titanium dioxide photocatalyst loaded with platinum nanoparticles and its application in photocatalytic reduction of nitrogen oxides to synthesize ammonia. Background Art
[0002] At present, as the most mature and effective NOx control technology, selective catalytic reduction technology (SCR) can achieve efficient catalytic conversion of NOx into harmless and stable N2. However, the SCR process still has the problem of secondary carbon emissions caused by heat supply and reductant consumption. In addition, the latest research confirms that the redox barrier of NOx is significantly lower than that of highly inert N2 molecules, and NOx has become an excellent N precursor resource. Therefore, finding and developing green and efficient new technologies for NOx control and resource utilization has become one of the most promising research directions for achieving ecological nitrogen cycle balance.
[0003] In recent years, solar-driven photocatalytic technology has received extensive attention in achieving green and efficient NOx harmless treatment. However, the photocatalytic NOx oxidation product NO3ˉ has secondary pollution problems, which not only forms secondary aerosol pollution, but also affects the acidity of precipitation, thereby causing water pollution. Therefore, the photocatalytic oxidation route with NO3ˉ as the final product is not the best NOx harmless treatment route. In comparison, the NOx deep reduction route is a more feasible reaction route, which can photocatalytically reduce NOx to NH3, which can not only effectively avoid the secondary pollution problem, but also achieve the high-value conversion of air pollutants to high-value-added chemicals. However, it is worth noting that most of the research on NOx reduction and ammonia synthesis is carried out in a liquid phase reaction system. Considering the inherent property that NO molecules are extremely difficult to dissolve in water, the liquid phase ammonia synthesis process of NOx has an efficiency bottleneck. The gas-solid phase photocatalytic reaction system can effectively avoid the above problems and simplify the complex "gas-liquid-solid" three-phase reaction process into a "gas-solid" two-phase reaction system. In addition, considering the actual emission occasions of flue gas NOx, the development of a gas-solid phase catalytic system is closer to the actual application scenario. However, to date, there are few reports on the gas-solid phase photocatalytic NOx reduction to synthesize ammonia.
[0004] Therefore, there is a need for a Pt nanoparticle-loaded TiO2 photocatalyst that can photocatalytically reduce NOx to synthesize ammonia in the gas-solid phase. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a Pt nanoparticle-loaded TiO2 photocatalyst and a method for synthesizing ammonia by reducing NOx using gas-solid phase photocatalysis.
[0006] The present invention is achieved in this way: a Pt nanoparticle-loaded TiO2 photocatalyst takes TiO2 as the core and loads Pt nanoparticles on its surface through a precipitation method or an impregnation method. The Pt nanoparticles are synthesized from a H2PtCl6 precursor.
[0007] Furthermore, the amount of Pt nanoparticles loaded on the TiO2 surface is adjustable.
[0008] Further, the Pt nanoparticle-loaded TiO2 photocatalyst is prepared by a precipitation method, comprising: S1, TiO2 powder was added into 100 ml of chloroplatinic acid (H2PtCl6·H2O) solution with different concentrations.
[0009] S2, the pH of the slurry was adjusted to 7 with 10% NaOH.
[0010] S3, placed at room temperature for 6 h, repeatedly washed with deionized water, centrifuged, and dried at 100 °C.
[0011] S4, the obtained sample was calcined in a muffle furnace at 400 °C for 2 h to obtain Pt nanoparticle-loaded TiO2 photocatalyst.
[0012] Further, the Pt nanoparticle-loaded TiO2 photocatalyst is prepared by an impregnation method, comprising S1, place P25 in a beaker and add 100 mL of deionized water.
[0013] S2, add a certain volume of H2PtCl6·H2O solution while stirring so that the concentration of H2PtCl6·H2O in the solution is 1.92-96 mg / 100 m.
[0014] S3, stirring continuously for 48 h, and baking in an oven at 80 °C for 24 h to obtain Pt nanoparticle-loaded TiO2 photocatalyst.
[0015] Another object of the present invention is to provide a Pt nanoparticle-loaded TiO2 photocatalyst for use in gas-solid phase photocatalytic NOx reduction to synthesize ammonia.
[0016] Further, the method for synthesizing ammonia by reducing NOx using the Pt nanoparticle-supported TiO2 photocatalyst in a gas-solid phase photocatalytic manner is as follows: S1, Pt nanoparticles loaded with TiO2 photocatalyst were uniformly dispersed in a small amount of deionized water solution and ultrasonicated for 5 minutes to fully dissolve the sample in deionized water.
[0017] S2, the mixed solution is evenly coated on the glass fiber membrane, and the coated glass fiber membrane is placed in a vacuum oven at 60° C. and continuously vacuumed for 8 h to remove excess deionized water on the glass fiber membrane.
[0018] S3, introducing NOx gas into the front end of the reaction chamber.
[0019] Furthermore, the concentration of NOx in the reaction system is 100 ppm-1000 ppm.
[0020] Furthermore, the flow rate of NOx in the reaction system is 4 ml / min-20 ml / min.
[0021] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows: First, the present invention has completed the experimental path of NOx gas-solid phase ammonia synthesis for the first time, avoiding the efficiency bottleneck caused by the inherent property of NO molecules being extremely insoluble in water in the liquid phase reaction system. The complex "gas-liquid-solid" three-phase reaction process is simplified to a "gas-solid" two-phase reaction system. In addition, considering the actual emission occasions of flue gas NOx, the development of a gas-solid phase catalytic system is closer to the actual application scenario.
[0022] The present invention discloses a novel method for gas-solid phase photocatalytic NOx reduction and efficient ammonia synthesis based on Pt nanoparticle-loaded TiO2 photocatalyst. The Pt nanoparticles in the Pt nanoparticle-loaded TiO2 photocatalyst have strong dissociation ability for H2O, which solves the problem of H2O removal in gas-solid phase NOx photocatalytic ammonia synthesis. + The problem of difficult protonation promotes the combination of NOx and H ions, which gradually react to synthesize ammonia, thereby greatly enhancing the conversion rate and selectivity of photocatalytic NOx reduction to synthesize ammonia.
[0023] Second, the expected benefits and commercial value of the technical solution of the present invention after transformation are as follows: According to GB 13223-2011 “Emission Standards of Air Pollutants from Thermal Power Plants”, the NOx in the flue gas emitted by the treated coal-fired power plant is about 100 mg m -3 , while the NOx content of untreated flue gas can reach 500-1000 ppm (converted to pure NO). The present invention realizes the technical accumulation of photocatalytic technology for actual flue gas control and resource utilization route.
[0024] The technical solution of the present invention fills the technical gap in the industry at home and abroad: the present invention completes the experimental path of NOx gas-solid phase synthesis of ammonia for the first time, avoiding the efficiency bottleneck caused by the inherent property of NO molecules being extremely difficult to dissolve in water in the liquid phase reaction system. The complex "gas-liquid-solid" three-phase reaction process is simplified to a "gas-solid" two-phase reaction system. In addition, considering the actual emission occasions of flue gas NOx, the development of a gas-solid phase catalytic system is closer to the actual application scenario.
[0025] The technical solution of the present invention solves a technical problem that people have been eager to solve but have never been successful: unlike the proton-rich liquid phase reaction environment, the source of protons at the gas-solid phase reaction interface depends on the protonation process of H2O. However, due to the constraints of H2O protonation and proton-coupled multi-electron transfer processes, the supply efficiency of electrons and protons is low, which also leads to a large room for improvement in the overall efficiency and product selectivity of the NOx gas-solid phase conversion pathway. The present invention develops a high-efficiency catalyst, and improves the H2O protonation ability of the catalyst by regulating the active sites, and promotes the proton-coupled multi-electron transfer process, which will be the key to our successful research on efficient gas-solid phase photocatalytic NOx reduction and ammonia synthesis.
[0026] The problem of H2O not being able to be efficiently protonated in gas-solid phase reactions was overcome, and an efficient gas-solid phase photocatalytic NOx reduction to ammonia synthesis reaction pathway was successfully constructed.
[0027] Third, the technical solution of the present invention aims at improving the performance of existing photocatalysts, and proposes a Pt nanoparticle-loaded TiO2 photocatalyst, and loads Pt nanoparticles on the surface of TiO2 by precipitation or impregnation. Compared with traditional technologies, the following aspects reflect the significant technical progress of the present invention: 1. Higher catalytic activity: By loading Pt nanoparticles, the photocatalytic performance of TiO2 can be effectively enhanced, especially in the photolysis of water, degradation of organic pollutants and other reactions. Pt, as a noble metal, can significantly improve the charge separation efficiency on the TiO2 surface, reduce the recombination rate of electrons and holes, and thus improve the photocatalytic efficiency.
[0028] 2. Adjustable loading quantity: The technical solution of adjustable loading quantity of Pt nanoparticles proposed in the present invention can adjust the quantity of Pt particles according to different catalytic requirements and further optimize the performance of the photocatalyst. By changing the concentration of H2PtCl6 solution, the size and distribution of Pt particles can be precisely controlled to ensure the efficient catalytic reaction.
[0029] 3. Simplicity and controllability of the preparation method: Precipitation and impregnation are two simple and economical preparation techniques. In the precipitation method, the pH value of the NaOH solution is adjusted to ensure uniform deposition of Pt nanoparticles; in the impregnation method, stirring and temperature control are used to promote uniform loading of Pt particles. These methods can effectively control the structure and performance of the catalyst and reduce production costs.
[0030] 4. Catalyst stability: Through high-temperature calcination and heat treatment, the catalyst of the present invention has good thermal stability and long-term catalytic activity, and can maintain a high catalytic efficiency under high temperature and light environment, overcoming the problem of performance degradation of traditional TiO2 catalysts during long-term use.
[0031] 5. Environmentally friendly: The present invention uses environmentally friendly H2PtCl6·H2O as a precursor to ensure the green nature of the catalyst preparation process. In addition, TiO2 itself has a good ability to photocatalytically degrade organic pollutants. Combined with the loading of Pt nanoparticles, it can effectively address environmental pollution problems and achieve green chemical reactions.
[0032] In summary, the present invention not only provides a Pt nanoparticle-loaded TiO2 photocatalyst with better performance and simple preparation, but also achieves performance optimization by adjusting the number and distribution of Pt particles, significantly improves the catalytic efficiency, and meets the needs in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a flow chart of preparing Pt nanoparticle-loaded TiO2 photocatalyst by precipitation method provided in an embodiment of the present invention.
[0034] Figure 2 It is the XRD diagram (XRD is the abbreviation of X-ray Diffraction) of the Pt nanoparticle-loaded TiO2 photocatalyst prepared in Example 1 of the present invention and the original TiO2 photocatalyst.
[0035] Figure 3 This is the XPS graph of the Pt nanoparticle-loaded TiO2 photocatalyst prepared in Example 1 of the present invention (XPS is the abbreviation of X-ray Photoelectron Spectroscopy).
[0036] Figure 4 This is a low-magnification TEM image (TEM is the abbreviation of Transmission Electron Microscope) of the Pt nanoparticle-loaded TiO2 photocatalyst prepared in Example 1 of the present invention.
[0037] Figure 5 This is a high-magnification TEM image (TEM is the abbreviation of High Resolution Transmission Electron Microscope, i.e., transmission electron microscope) of the Pt nanoparticle-loaded TiO2 photocatalyst prepared in Example 1 of the present invention.
[0038] Figure 6 It is the XANES graph of the Pt nanoparticle-loaded TiO2 photocatalyst prepared in Example 1 of the present invention under different reaction conditions (XANES is the abbreviation of X-ray Absorption Near Edge Structure).
[0039] Figure 7 It is a DFT calculation path diagram (DFT is Density Functional Theory) of the Pt nanoparticle-loaded TiO2 photocatalyst prepared in Example 1 of the present invention and the original TiO2 photocatalyst in the process of NOx reduction and ammonia synthesis.
[0040] Figure 8 This is a comparison chart of the NOx photocatalytic conversion activities of the Pt nanoparticle-loaded TiO2 photocatalyst prepared in Example 1 of the present invention and the original TiO2 photocatalyst.
[0041] Fig. 9 This is a comparison chart of the selectivity of the Pt nanoparticle-loaded TiO2 photocatalyst prepared in Example 1 of the present invention and the original TiO2 photocatalyst for photocatalytic conversion of NOx into ammonia.
[0042] Fig.10 This is a stability test chart of the photocatalytic NOx reduction and ammonia synthesis by the Pt nanoparticle-loaded TiO2 photocatalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0044] An embodiment of the present invention provides a titanium dioxide (TiO2) photocatalyst loaded with platinum (Pt) nanoparticles, which takes TiO2 as the core and loads Pt nanoparticles on its surface by precipitation or impregnation. The number of Pt nanoparticles loaded on the TiO2 surface is adjustable, and the Pt nanoparticles are synthesized from a chloroplatinic acid (H2PtCl6) precursor.
[0045] Example 1: Preparation of TiO2 modified with platinum oxide by precipitation method 8 g of TiO2 powder was accurately weighed and added to 100 ml of chloroplatinic acid hydrate (H2PtCl6·H2O) solution (concentration 9.6 mg / 100 ml) to prepare a Pt nanoparticle-loaded TiO2 photocatalyst with a loading of 0.12%. The slurry was adjusted to pH 7 with 10% sodium hydroxide (NaOH), then placed at room temperature for 6 h, repeatedly washed with deionized water, centrifuged, and dried at 100 °C. The obtained sample was calcined in a muffle furnace at 400 °C for 2 h, and finally a Pt nanoparticle TiO2 photocatalyst with a loading of 0.12% (0.12%-Pt-TiO2) was obtained.
[0046] The Pt nanoparticle-loaded TiO2 photocatalyst prepared in Example 1 of the present invention was characterized, and it was found that the Pt nanoparticle-loaded TiO2 photocatalyst had the following characteristics: XRD analysis of Pt nanoparticles-loaded TiO2 photocatalyst and pristine TiO2 photocatalyst, such as Figure 2 As shown; the Pt nanoparticle-loaded TiO2 photocatalyst has a complete TiO2 crystal structure, and the surface-loaded Pt nanoparticle TiO2 photocatalyst crystal structure has not changed at all.
[0047] like Figure 3 Shown is the XPS graph of the Pt 4f fine spectrum of the Pt nanoparticle-loaded TiO2 photocatalyst and the original TiO2 photocatalyst, from which the XPS characteristic peak of Pt can be detected, proving that the Pt nanoparticles are successfully loaded in TiO2.
[0048] like Figure 4 The figure shows a low-magnification TEM image of a Pt nanoparticle-loaded TiO2 photocatalyst. The bright spots in the image are Pt nanoparticles, proving that the Pt nanoparticles are uniformly loaded on TiO2. This proves the successful synthesis of the Pt nanoparticle-loaded TiO2 photocatalyst.
[0049] like Figure 5 The figure shows a high-magnification TEM image of a Pt nanoparticle-loaded TiO2 photocatalyst. The lattice fringes of the Pt nanoparticles are 3.058 Å. This matches the PDF card of the XRD of PtO. This proves that Pt exists in the form of 2+ on the catalyst surface.
[0050] XANES test of Pt nanoparticle-supported TiO2 photocatalyst during NOx gas-solid phase reduction, such as Figure 6 As shown, the results indicate that during the reaction, there is a strong interaction between Pt nanoparticles loaded with TiO2 photocatalyst and NOx. Pt nanoparticles have a strong ability to pull electrons, pulling electrons in the TiO2 bulk phase to the surface to fully participate in the reaction. At the same time, the valence state of Pt nanoparticles changes from 2+ to low valence.
[0051] The DFT path calculation was performed on the process of NOx gas-solid phase photocatalytic reduction of ammonia by Pt nanoparticles loaded with TiO2 photocatalyst and TiO2 photocatalyst provided in Example 1 of the present invention, and it was confirmed that the Pt nanoparticles loaded with TiO2 photocatalyst and TiO2 photocatalyst can reduce NOx to NH4. + Pt nanoparticles loaded with TiO2 photocatalyst can optimize the reduction of NOx to NH4 +The reaction path of NOx is shortened and NOx is more easily combined with H protons, which is crucial for the NOx synthesis ammonia reaction. The adsorption barrier of Pt nanoparticle-loaded TiO2 photocatalyst to NOx is lower than that of TiO2 photocatalyst, indicating that the presence of Pt nanoparticles can promote NOx adsorption. More NOx is adsorbed on the catalyst surface, and more subsequent reactions will take place.
[0052] NOx conversion rate and NH4 in ammonia synthesis system by gas-solid NOx reduction + The generation amount and selectivity are used to test the catalytic performance of the Pt nanoparticle-loaded TiO2 photocatalyst and the TiO2 photocatalyst for NOx reduction and ammonia synthesis provided in Example 1 of the present invention. It is worth noting that the gas-solid phase NOx reduction and ammonia synthesis reaction system is also a part of the present invention, and the test process is as follows: 15 mg of Pt nanoparticles loaded with TiO2 photocatalyst or TiO2 photocatalyst prepared in the example were uniformly dispersed in a small amount of deionized water solution and ultrasonicated for 5 minutes to fully dissolve the sample in the deionized water. The mixed solution was uniformly coated on a glass fiber membrane with a radius of 1.0 cm and a pore size of 0.25 μm. The coated glass fiber membrane was placed in a vacuum oven and continuously evacuated at 60°C for 8 h to remove excess deionized water on the glass fiber membrane.
[0053] The catalyst was tested for its catalytic performance in NOx reduction and ammonia synthesis in an innovative reaction circuit. The entire reaction was carried out in the gas-solid phase, without involving liquid phase reactions. A NOx gas with a concentration of 100 ppm-1000 ppm was introduced into the front end of the reaction chamber, and the flow rate of NOx was 4 ml / min-20 ml / min. A large amount of alkaline solution was provided in the reaction chamber to absorb the NH4 generated during the catalytic process. + The reaction chamber is completely sealed, and a quartz plate is used as a light port at the top to irradiate the reaction. The rear end of the reaction chamber is connected to a flue gas analyzer to test the NOx concentration in real time and determine the NOx conversion rate. Finally, the alkaline liquid in the reaction chamber is collected, and the amount of ammonia generated during the entire reaction cycle is determined by cation chromatography, and the selectivity of NOx reduction to synthesize ammonia is calculated by N conservation.
[0054] The Pt nanoparticle-loaded TiO2 photocatalyst and the NOx gas-solid phase conversion activity of the TiO2 photocatalyst provided in Example 1 of the present invention are as follows: Figure 8 As shown in the figure, the conversion rate of Pt nanoparticles loaded TiO2 photocatalyst to NOx is 62%, while the conversion rate of TiO2 photocatalyst to NOx is 18%. The experiment proves that the catalytic efficiency of Pt nanoparticles loaded TiO2 photocatalyst in gas-solid phase NOx reduction and ammonia synthesis is increased by 3.44 times compared with TiO2 photocatalyst.
[0055] like Fig. 9 As shown, the concentration and selectivity calculation of the NOx gas-solid phase photocatalytic reduction synthesis of ammonia were performed on the Pt nanoparticle-loaded TiO2 photocatalyst and the TiO2 photocatalyst provided in Example 1 of the present invention. The Pt nanoparticle-loaded TiO2 photocatalyst reacted to generate 17.2 mg / L of NH4 + . It is 10 times the amount of ammonia generated by TiO2 photocatalyst reaction. In terms of selectivity, the selectivity of Pt nanoparticles loaded with TiO2 photocatalyst to generate ammonia is 86.3%, while the selectivity of TiO2 photocatalyst to generate ammonia is only 30.1%. It greatly improves the selectivity of NOx reduction to generate ammonia, and solves the problem of low selectivity of gas-solid phase NOx reduction to synthesize ammonia.
[0056] like Fig.10 As shown, the cyclic stability of the Pt nanoparticle-loaded TiO2 photocatalyst provided in Example 1 of the present invention in the NOx gas-solid phase photocatalytic reduction of ammonia synthesis reaction system was tested, and four consecutive catalytic reactions were carried out on the Pt nanoparticle-loaded TiO2 photocatalyst. The results showed that the Pt nanoparticle-loaded TiO2 photocatalyst can remain stable in NOx without any poisoning phenomenon.
[0057] Example 2: Preparation of 0.12% Pt nanoparticles TiO2 by impregnation method Accurately weigh 8 g of P25 and place it in a beaker. Add 100 mL of deionized water and add a certain volume of H2PtCl6·H2O solution while stirring so that the concentration of H2PtCl6·H2O in the solution is 9.6 mg / 100 m. Stir continuously for 48 h and bake in an oven at 80°C for 24 h to finally obtain a Pt nanoparticle TiO2 photocatalyst with a loading of 0.12% (0.12%-Pt-TiO2).
[0058] Example 3: Gas-solid phase NOx reduction ammonia synthesis reaction device 100 ppm-1000 ppm NOx gas is continuously introduced into the front end of the reaction chamber, and a large amount of alkaline solution is provided in the reaction chamber to absorb the NH4 generated during the catalytic process. + The reaction chamber is completely sealed, and a quartz plate is used as a light port at the top to irradiate the reaction. The rear end of the reaction chamber is connected to a flue gas analyzer to test the NOx concentration in real time and determine the NOx conversion rate. Finally, the alkaline liquid in the reaction chamber is collected, and the amount of ammonia generated during the entire reaction cycle is determined by cation chromatography, and the selectivity of NOx reduction to synthesize ammonia is calculated by N conservation.
[0059] The Pt nanoparticle-loaded TiO2 photocatalyst of the present invention is realized by loading Pt nanoparticles on the core surface of TiO2 by a precipitation method or an impregnation method. The specific synthesis steps are as follows: first, TiO2 powder is added to H2PtCl6·H2O solutions of different concentrations to make the Pt precursor fully contact with the TiO2 surface. Then, the pH value of the mixed slurry is adjusted to 7 using a 10% NaOH solution to cause the Pt nanoparticles to precipitate or uniformly disperse on the TiO2 surface. Subsequently, the mixture is placed at room temperature for 6 hours to completely reduce the Pt precursor and fix it on the TiO2 surface. Unreacted impurities and by-products are removed by repeated washing with deionized water and centrifugal treatment, and finally the sample is dried at 100°C. The dried sample is calcined in a muffle furnace at 400°C for 2 hours to complete the fixation of the Pt nanoparticles and the optimization of the TiO2 crystal structure, thereby obtaining an efficient Pt-loaded TiO2 photocatalyst.
[0060] Loading Pt nanoparticles on the TiO2 surface not only enhances the surface area of the photocatalyst, but also significantly improves its electron-hole pair separation efficiency. Pt, as a precious metal nanoparticle, has excellent electrical conductivity and catalytic activity, and can form Schottky junctions on the TiO2 surface, acting as electron capture centers. When TiO2 absorbs photons, the generated electrons are quickly captured by Pt nanoparticles, reducing the recombination probability of electrons and holes. This mechanism effectively prolongs the lifetime of electrons and holes and improves the efficiency of the photocatalytic reaction. In addition, by adjusting the concentration of the H2PtCl6·H2O solution, the number of Pt nanoparticles loaded on the TiO2 surface can be precisely controlled, further optimizing the performance of the photocatalyst to meet the needs of different application scenarios.
[0061] Pt nanoparticles loaded with TiO2 photocatalysts show excellent performance in photocatalytic reactions. As a semiconductor photocatalyst, TiO2 can generate electron-hole pairs under ultraviolet light irradiation. These active species can oxidize organic pollutants or reduce harmful substances in the environment. However, TiO2 itself has the defect of electron-hole pair recombination, which limits its photocatalytic efficiency. The introduction of Pt nanoparticles greatly reduces the recombination phenomenon by promoting the effective migration and separation of electrons, thereby significantly improving the photocatalytic activity. In addition, Pt nanoparticles can also catalyze the generation and conversion of reaction intermediates, further accelerate the photocatalytic reaction rate, and improve the overall catalytic efficiency, making it have broad application prospects in the fields of environmental governance and organic pollutant degradation.
[0062] The Pt nanoparticle-loaded TiO2 photocatalyst of the present invention exhibits significant technical advantages in multiple industrial fields due to its efficient photocatalytic performance and adjustable Pt loading. First, its application in environmental pollution control, such as organic wastewater treatment and air purification, can efficiently degrade harmful organic matter and improve environmental quality. Secondly, in the field of energy, it is used as a photocatalyst for photolysis of water to produce hydrogen, providing a clean energy solution. Furthermore, by adjusting the loading amount of Pt nanoparticles, the performance of the catalyst can be optimized to meet different application requirements and enhance its market competitiveness. In addition, the preparation method using precipitation or impregnation is simple and cost-controllable, suitable for large-scale industrial production, and promotes green chemical industry and sustainable development. Therefore, the Pt nanoparticle-loaded TiO2 photocatalyst of the present invention has achieved significant technical progress in improving photocatalytic efficiency, expanding application fields, and achieving economic feasibility, and has a wide range of industrial application prospects and promotion value.
[0063] The present invention significantly improves the performance of TiO2 photocatalyst by loading Pt nanoparticles on the TiO2 surface and utilizing its excellent electron capture ability and catalytic activity. Combined with the adjustable Pt loading amount and simple preparation method, the photocatalyst has shown wide application potential and significant technical advantages in multiple industrial fields such as environmental governance and energy conversion, promoting the further development and industrialization of photocatalytic technology.
[0064] The present invention has completed the experimental path of NOx gas-solid phase synthesis of ammonia for the first time, and disclosed a new method for gas-solid phase photocatalytic NOx reduction and efficient synthesis of ammonia based on Pt nanoparticle-loaded TiO2 photocatalyst. The Pt nanoparticles in the Pt nanoparticle-loaded TiO2 photocatalyst have strong dissociation ability for H2O, which solves the problem of H2O in gas-solid phase NOx photocatalytic synthesis of ammonia. + The problem of difficult protonation promotes the combination of NOx and H ions, which gradually react to synthesize ammonia, thereby greatly enhancing the conversion rate and selectivity of photocatalytic NOx reduction to synthesize ammonia.
[0065] The Pt nanoparticle-loaded TiO2 photocatalyst and the NOx gas-solid phase conversion activity of the TiO2 photocatalyst provided in Example 1 of the present invention are as follows: Figure 8 As shown in the figure, the conversion rate of Pt nanoparticles loaded TiO2 photocatalyst to NOx is 62%, while the conversion rate of TiO2 photocatalyst to NOx is 18%. The experiment proves that the catalytic efficiency of Pt nanoparticles loaded TiO2 photocatalyst in gas-solid phase NOx reduction and ammonia synthesis is increased by 3.44 times compared with TiO2 photocatalyst.
[0066] like Fig. 9As shown, the concentration and selectivity calculation of the NOx gas-solid phase photocatalytic reduction synthesis of ammonia were performed on the Pt nanoparticle-loaded TiO2 photocatalyst and the TiO2 photocatalyst provided in Example 1 of the present invention. The Pt nanoparticle-loaded TiO2 photocatalyst reacted to generate 17.2 mg / L of NH4 + . It is 10 times the amount of ammonia generated by TiO2 photocatalyst reaction. In terms of selectivity, the selectivity of Pt nanoparticles loaded with TiO2 photocatalyst to generate ammonia is 86.3%, while the selectivity of TiO2 photocatalyst to generate ammonia is only 30.1%. It greatly improves the selectivity of NOx reduction to generate ammonia, and solves the problem of low selectivity of gas-solid phase NOx reduction to synthesize ammonia.
[0067] like Fig.10 As shown, the cyclic stability of the Pt nanoparticle-loaded TiO2 photocatalyst provided in Example 1 of the present invention in the NOx gas-solid phase photocatalytic reduction of ammonia synthesis reaction system was tested, and four consecutive catalytic reactions were carried out on the Pt nanoparticle-loaded TiO2 photocatalyst. The results showed that the Pt nanoparticle-loaded TiO2 photocatalyst can remain stable in NOx without any poisoning phenomenon.
[0068] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A Pt nanoparticle-loaded TiO2 photocatalyst, characterized in that: Taking TiO2 as the core, Pt nanoparticles are loaded on its surface by precipitation method or impregnation method, and the Pt nanoparticles are synthesized from H2PtCl6 precursor.
2. The Pt nanoparticle-supported TiO2 photocatalyst according to claim 1, characterized in that: The amount of Pt nanoparticles loaded on the TiO2 surface is adjustable.
3. The Pt nanoparticle-supported TiO2 photocatalyst according to claim 1, characterized in that: The method for preparing a Pt nanoparticle-loaded TiO2 photocatalyst comprises: S1, TiO2 powder was added into 100 ml H2PtCl6·H2O solution with different concentrations; S2, the pH of the slurry was adjusted to 7 with 10% NaOH; S3, placed at room temperature for 6 h, repeatedly washed with deionized water, centrifuged, and dried at 100 °C; S4, the obtained sample was calcined in a muffle furnace at 400 °C for 2 h to obtain Pt nanoparticle-loaded TiO2 photocatalyst.
4. The Pt nanoparticle-supported TiO2 photocatalyst according to claim 1, characterized in that: The impregnation method is used to prepare a Pt nanoparticle-loaded TiO2 photocatalyst, comprising: S1, place P25 in a beaker and add 100 mL of deionized water; S2, adding a certain volume of H2PtCl6·H2O solution while stirring, so that the concentration of H2PtCl6·H2O in the solution is 1.92-96 mg / 100 m; S3, stirring continuously for 48 h, and baking in an oven at 80 °C for 24 h to obtain Pt nanoparticle-loaded TiO2 photocatalyst.
5. Use of the Pt nanoparticle-supported TiO2 photocatalyst as claimed in any one of claims 1 to 4 in gas-solid phase photocatalytic NOx reduction to synthesize ammonia.
6. A method for synthesizing ammonia by reducing NOx in a gas-solid phase using a Pt nanoparticle-supported TiO2 photocatalyst as claimed in claim 5, comprising: S1, Pt nanoparticles loaded with TiO2 photocatalyst were uniformly dispersed in a small amount of deionized water solution, and ultrasonicated for 5 minutes to fully dissolve the sample in deionized water; S2, coating the mixed solution evenly on the glass fiber membrane, placing the coated glass fiber membrane in a vacuum oven at 60°C for 8 h to remove excess deionized water on the glass fiber membrane; S3, introducing NOx gas into the front end of the reaction chamber.
7. The method for synthesizing ammonia by reducing NOx using a TiO2 photocatalyst supported by Pt nanoparticles in a gas-solid phase photocatalytic manner as claimed in claim 6, characterized in that: The concentration of NOx in the reaction system is 100 ppm-1000 ppm.
8. The method for synthesizing ammonia by reducing NOx using a TiO2 photocatalyst supported by Pt nanoparticles in a gas-solid phase photocatalytic manner as claimed in claim 6, characterized in that: The flow rate of NOx in the reaction system is 4 ml / min-20 ml / min.
Citation Information
Patent Citations
Catalyst for catalytic oxidation of gaseous hydrogen tritide, and preparation method and application of catalyst
CN103831098A
Platinum based catalyst and preparation method thereof, monolithic catalyst containing platinum based catalyst and application thereof
CN107583641A
Preparation method and application of cotton-fiber-like TiO2 loaded with Pt nanoparticles
CN108325519A
Catalyst for NO oxide ammonia synthesis and preparation method and application thereof,
CN113786842A
Pd / ferroferric oxide catalyst for photo-assisting NO to generate ammonia as well as preparation method and application of Pd / ferroferric oxide catalyst
CN115301253A